2006
DOI: 10.1097/00000478-200606000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Carcinoma of the Prostate: An Immunohistochemical Study

Abstract: Small cell carcinoma of the prostate (SCPC) is morphologically similar to small cell carcinoma of the lung (SCLC) and maybe misinterpreted as Gleason pattern 5b prostate adenocarcinoma (HGPC). Recognition of SCPC is important because of its different clinical behavior. This study aims to characterize the immunophenotype of histologically classic SCPC using a comprehensive panel of markers, to better understand its histogenesis, aid in its classification, and evaluate potential therapeutic targets. Using the Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(147 citation statements)
references
References 49 publications
3
138
1
1
Order By: Relevance
“…To establish an accurate diagnosis of nodal Merkel cell carcinoma can be challenging due to lack of cutaneous presentation and presence of a broad [50][51][52] The distinction between nodal Merkel cell carcinoma and small cell melanoma is usually straightforward as melanoma cells express S100 and other melanocytic markers (HMB45, MITF, and MART1).…”
Section: Differential Diagnosis Of Nodal Merkel Cell Carcinomamentioning
confidence: 99%
“…To establish an accurate diagnosis of nodal Merkel cell carcinoma can be challenging due to lack of cutaneous presentation and presence of a broad [50][51][52] The distinction between nodal Merkel cell carcinoma and small cell melanoma is usually straightforward as melanoma cells express S100 and other melanocytic markers (HMB45, MITF, and MART1).…”
Section: Differential Diagnosis Of Nodal Merkel Cell Carcinomamentioning
confidence: 99%
“…[20][21][22] These criteria include a proliferation of small cells (>4 lymphocytes in diameter) with unique and strict morphological features, scant cytoplasm, ill-defined borders, finely granular 'salt and pepper' chromatin, absent or inconspicuous nucleoli, frequent nuclear molding, and a high mitotic count. Morphological variations of prostatic SCC include intermediate-cell-type tumours with slightly-more-open chromatin and visible small nucleoli seen in about 30-40% of cases-tumours that would probably not be included in the strict diagnosis of SCC of the lung.…”
Section: Pathological Featuresmentioning
confidence: 99%
“…Wang et al reported a rate of 94%, being CD56 the most sensitive (7). One caveat is that conventional adenocarcinomas, up to 100% in some studies, may focally express these same markers, reinforcing the need for careful morphologic evaluation by the pathologist (5,15,16). More recent discoveries have suggested that prostatic specific membrane antigen (PSMA), CD44 and protein (P501S) may help with indentifying neuroendocrine expression in tumors (7,17).…”
Section: Discussionmentioning
confidence: 99%